2007
DOI: 10.1007/s00464-007-9406-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic ventral hernia repair in morbidly obese patients with a body mass index exceeding 35 kg/m2

Abstract: For morbidly obese patients, LVHR is safe and effective, but it is associated with higher likelihood of recurrence, and patients should be appropriately informed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 9 publications
0
32
0
1
Order By: Relevance
“…It is reported that even a modest 10% reduction of excess body weight before elective surgery significantly reduces obesity-related risks associated with anesthesia, pulmonary dysfunction, diabetes and hypertension, and other comorbid physiologic conditions [10]. These concepts have been so well established that overweight, obesity, and morbid obesity are now relative contraindications to such procedures as hernia repair, joint replacement, and organ transplantation [1][2][3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that even a modest 10% reduction of excess body weight before elective surgery significantly reduces obesity-related risks associated with anesthesia, pulmonary dysfunction, diabetes and hypertension, and other comorbid physiologic conditions [10]. These concepts have been so well established that overweight, obesity, and morbid obesity are now relative contraindications to such procedures as hernia repair, joint replacement, and organ transplantation [1][2][3][4][5].…”
mentioning
confidence: 99%
“…Studies show that excess weight and all spectrums of obesity complicate the shortand long-term outcomes of surgical interventions in a variety of ways [1][2][3][4][5][6][7][8][9]. It is reported that even a modest 10% reduction of excess body weight before elective surgery significantly reduces obesity-related risks associated with anesthesia, pulmonary dysfunction, diabetes and hypertension, and other comorbid physiologic conditions [10].…”
mentioning
confidence: 99%
“…• Morbid obesity [324], old age, and debilitation are not considered contraindications to laparoscopy (LE 4) [321,325].…”
Section: Ventral Herniasmentioning
confidence: 99%
“…While some of these studies looked at outcomes such as length of stay and recurrence, others investigated metrics related to quality of care such as postoperative wound complications. However, specific limitations such as using patients from a single institution (n < 150) and excluding obese patients with BMI's between 25-35 [11,12] contribute to some uncertainty in these studies findings. Furthermore, even though the remaining studies used larger databases, they either included inguinal hernias in addition to ventral hernias [10] or only looked VHR procedures from 2009-2012 in the context of open versus laparoscopic repair.…”
mentioning
confidence: 99%
“…A number of recent studies have found an association between obesity and post-operative complications after ventral hernia repair [9][10][11][12]. While some of these studies looked at outcomes such as length of stay and recurrence, others investigated metrics related to quality of care such as postoperative wound complications.…”
mentioning
confidence: 99%